Answer:
"the summation from n equals one to 6 of quantity negative 7 minus 3 times n"
Explanation:
General term of an arithmetic sequence:
![a_n=a_1+(n-1)r](https://img.qammunity.org/2020/formulas/mathematics/middle-school/rj34j8icuf2rpym71ol5d17ltaxthyadfw.png)
Where
is the first term
n is the number of terms
r is the common difference
The value of r can be found by subtracting two consecutive values
![r=a_2-a_1=-13+10=-3](https://img.qammunity.org/2020/formulas/mathematics/middle-school/t7rz7wb3i107ivahd6n0q5ghplmgknmykp.png)
Then
![a_n=-10+(n-1)(-3)=-7-3n](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ro78bk51al0wk3inceun94gu2bbd143sv9.png)
If we want to sum the first six terms of the sequence, we must find
![\sum_(n=1)^(n=6)(-7-3n)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/j41pp1snuroauqqxdzk34ow29fg47gf9t9.png)
The correct option is
"the summation from n equals one to 6 of quantity negative 7 minus 3 times n"